Recent developments in the diagnosis and treatment of Addison's disease - Abed Alharbi, Samar; Fardan, Rawdha Hameed; Almahasnah, Mustafa Saeed; Alsaeed, Nouf Ali; Kashif, Hiba Hani; AlGhamdi, Nora Abdullah; Alharthi, Amani Awadh; Ghamdi, Sara Abdullah Al; Asiri, Amna Ayed; Alharbi, Dhari Ahmed (International Journal Of Community Medicine And Public Health, 2024)
Primary adrenal insufficiency (PAI), also referred to as Addison's disease (AD), is a rare but potentially life-threatening disorder marked by a deficiency in the production of hormones by the adrenal cortex. Despite significant advancements in diagnosis and treatment, challenges remain, particularly in pediatric cases where diagnostic delays are common. Autoimmune adrenalitis is the leading cause of AD in adults, while congenital adrenal hyperplasia (CAH) due to 21-hydroxylase deficiency is the primary cause in children. Recent developments include dual-release hydrocortisone formulations designed to mimic circadian rhythms and improve patient outcomes, as well as continuous subcutaneous cortisol infusion using insulin pumps. Experimental therapies, such as immunosuppression, gene therapy, and cell replacement, are in early stages of research. Management focuses on hormone replacement therapy and preventing adrenal crises, often triggered by infections or surgery. Education on crisis prevention is crucial, and patients should regularly monitor hormone levels. Advances in treatment aim to improve quality of life, yet more research is needed to refine therapeutic approaches and long-term outcomes.